Biosphere expansion drives Earth’s secular oxygenation while tectonics modulate oxygen variability revealed by machine learning - Zhen-Jie Zhang; Dong-Jie Tang; Qiu-Ming Cheng (Proceedings of the National Academy of Sciences, 2026)
The rise of atmospheric oxygen fundamentally transformed Earth’s surface environment and enabled the evolution of complex life. However, the processes driving long-term oxygen fluctuations remain poorly resolved, partly from limited proxy resolution and temporal coverage. Trace element (TE) concentrations in sedimentary pyrite offer a robust archive of redox conditions in ancient oceans and their linkage to atmospheric oxygen levels. Here we integrate high-resolution geochemical data from pyrite grains spanning 3.5 billion years with machine learning to reconstruct atmospheric oxygen evolution. We identify two coherent TE groups representing redox-sensitive and hydrothermal influences. Our results reveal that the long-term, secular trend of atmospheric oxygen is tightly coupled with biosphere expansion, whereas superimposed short-term fluctuations are influenced by tectonic events, including supercontinent assembly and breakup. Specifically, we show that primary oxygenation events (GOE and NOE) correlate strongly with biological expansion. Episodes of prolonged oxygenation broadly overlap with continental assembly, reflecting enhanced weathering, nutrient fluxes, and organic carbon burial, whereas supercontinent breakup phases are commonly associated with more reducing conditions, likely linked to increased volcanic emissions and diminished net biospheric oxygen. This reconstruction not only refines the temporal dynamics of Earth’s redox evolution but also highlights the interconnected roles of biological productivity, tectonics, ocean chemistry, and Earth-system processes in shaping planetary habitability. These findings provide a comprehensive framework for understanding Earth’s atmospheric evolution and inform models of environmental change on early Earth and other habitable planets.